Aspects of the biology and preliminary assessment of DNA quality and quantity of two cichlids from Lagos Lagoon, Nigeria - Olufemi O. Soyinka; Mutiu O. Sifau; Peace I. Adamu (Aceh Journal of Animal Science, 2022)
Aspects of the growth pattern, reproductive biology, and molecular characteristics of two cichlids, Sarotherodon melanotheron and Coptodon zillii were investigated in Lagos Lagoon. A total of twenty-nine individual species were collected from the Lagos Lagoon. Blood samples were obtained for DNA extraction and analysis from 9 specimens of each species. The morphometric data of S. melanotheron varied from 2.5-4.5cm (head length), 13.5-18.0cm (total length) and 35.00-135.00g (body weight), while that of C. zillii were 2.0-4.5cm, 12.0-21.5cm and 39.00-228.00g respectively. The growth pattern of S. melanotheron showed a positive allometric, b= 3.324, while that of C. zillii showed a negative allometric pattern with b= 2.715. The condition factors of S. melanotheron and C. zillii ranged from 4.15-4.55 and 4.12-5.07 respectively. The sex ratio for S. melanotheron was 1: 0.18, while C. zillii had a sex ratio of 1:0.33, and these were statistically significant (p 0.05). From the molecular characterization analysis, the DNA concentration ranged from 48-1265ng/µl and DNA purity ranged from 1.49-1.82. These findings form baseline information for conducting further investigations on the taxonomy, ecology, conservation of the genetic purity of these fisheries resources in Lagos Lagoon.